Perancangan Dan Pembuatan Alat Pengukur Skilu Dinamis Pada Jalan Rel Kereta Api - Atmaja, Dadang Sanjaya; Shakti, Panka Mahendra; Pratama, Martin Willy Eka (Politeknik Perkeretaapian Indonesia Madiun, 2017)
Checking elevation differences due to deflection on the railroad (skilu) is needed to ensure the safety of train travel. Skilu measurements can be done with a measuring train and a manual densometer. For manual measurement, we need tools that can measure dynamic elections more accurately and efficiently. This research is intended to make these tools using ultrasonic proximity sensors with data processing by a microcontroller. The measurement accuracy of the experimental results of this tool is obtained by comparing the densometer deflection gauge. The results show that the tool can measure elections every 0.1 second (realtime) with an accuracy rate of 98.84%. In addition to the election measurements, this tool can also measure the speed of a passing train and the rail temperature when a train passes. The measurement results can help optimize the care needed for the election that occurs at the observation site.